Research or "Cheerleading"? Scholarship on Community School District 2, New York City - Weiner, Lois (Education Policy Analysis Archives, 2003)
This article examines data on student achievement and school demographics not explored by the researchers who have promoted Community School District 2 (CSD 2) as a model of urban school reform that should be replicated elsewhere. Data on achievement indicate a remarkable degree of social and racial stratification among CSD 2's schools and levels of achievement that closely correlate with race, ethnicity, and poverty. In addition, when CSD 2's scores on state and city tests of mathematics are compared with results from CSD 25 in Queens, a school district that serves a population demographically similar, the superiority of its functioning becomes questionable. The article explains why the design of research on CSD 2 illustrates the perils to both research and policy when university-based researchers assume the role of “cheerleader” (Cuban, 1988), promoting reforms they have aided in implementing and assessing.